Peran Moeffreni Moe’min Dalam Pertempuran Front Timur Jakarta Tahun 1945-1949 - yeni yeni; Ahmad Sugiri; Muhamad Shoheh (Tsaqofah, 2018)
In the year of 1945-1949 Jakarta occupied by the Netherdlands. In occupation and the colonialism happen resistance by Jakarta community lead by scholars, youth, and bureaucrats. From among bureaucrats is Moeffreni Moe’min who is a military man. Struggle is Moefrreni Moe’min among them do sudden attack to East Front Jakarta at the date of 6 June 1946. During the Dutch period, Moeffreni Moe’min join fighters East Front Jakarta to defend the territory Jakarta; establish boundaries so that the Allies don’t expand the area; established intelligence forces to protect the people of Jakarta from sadistic acts carried out by NICA; embrace the army to defend independence; and fighting in the back line to seize allied weapons